Assessing The Clinical Correlation Between Acute Appendicitis And Histopathological Diagnosis - Dr. Muhammad Uzair Tariq , Dr. Saad Ul Khaliq , Dr. Ahmad Reshad Payenda , Dr. Noor Asad , Dr. Wasim Khan; Dr. Juwairiah-binte-Nawaz , Muhammad Rafay Khattak , Muhammad Umar , Dr. Usama Hidayat , Dr. Muhammad Uzair (Migration Letters, 2024)
Background: The most frequent reason for an acute abdomen that presents in the emergency room is acute appendicitis, which is primarily diagnosed based on clinical criteria. Objective: To evaluate the histological diagnosis and assess the diagnostic accuracy in a patient with acute appendicitis. Methods: At Northwest General Hospital and Research Center in Peshawar, Pakistan, this retrospective study was carried out between August 2021 and June 2022. The study comprised 104 patients who had an acute abdomen (an acute appendicitis diagnosis) at the time of presentation. Every successive patient had an appendectomy, and the intraoperative results, histopathological reports, and clinical diagnoses were compared. Results: The study comprised 104 patients in all who had appendicectomies throughout this time. The ag[1]e range of our patients was 16–53, and they arrived within 24 hours of the start of symptoms. The three most typical symptoms were anorexia, vomiting, and stomach pain. The predominant symptom was localized abdomen discomfort with a positive release sign. Gridiron was the most often made incision, followed by Lanz. There was gangrenous appendicitis in 12% of cases and acute appendiceal inflammation in 68%. There was a direct association between the time of presentation and the 3% perforation rate. Neither adenocarcinoma nor a carcinoid tumor affected any patients. Based on the histopathological findings, a negative appendicectomy rate of 15.0% indicated that 85% of the cases had acute appendicitis. Conclusion: The diagnosis of acute appendicitis can be made with clinical surgical competence alone, but additional diagnostic tools can improve the diagnostic accuracy. These tools are not always available and are not always 100% accurate. Therefore, a histopathology report can verify a correct diagnosis, which depends on sound clinical judgement.